GAMBARAN ANGKA KEJADIAN POST OPERATIVE NAUSEA AND VOMITING (PONV) PADA PASIEN YANG MENJALANI ANESTESI INHALASI DENGAN ISOFLURAN PADA BULAN OKTOBER - DESEMBER 2018 DI RSU PUTRI HIJAU TK. II KESDAM I/BB - MUHAMMAD IKHSAN; ANDRI YUNAFRI (LP2MTBM MAKARIOZ, 2020)
Post operative nausea and vomiting (PONV) occur in 24-48 hours after operative procedures. PONV is the commonestcause to disstressing/dissatisfying in patient during anaesthesia procedures. Unresolved PONV may result in prolonged PostAnesthesia Care Unit (PACU) and increasing readmission into the hospital. Result in overall health care costs. Reported thatincidence of PONV about 30% to 80% in high-risks patients. Around 30% of the 100 millions patient on the operativeprocedures in United States of America had PONV. In Indonesia, incidence of PONV not yet clearly recorded. To find out theincidence of PONV in terms of isoflurane use, gender, age, type of surgery, and smoking history in October-December 2018at RSU Putri Hijau Tk. II Kesdam I/BB. This study is descriptive-quantitative categorical by surveying medical record patientsundergone anaesthesia with isoflurane on October-December 2018 at RSU Putri Hijau Tk. II Kesdam I/BB. Of the 70 patientsusing inhalational anaesthesia with isoflurane, 27 patients experienced PONV (38,6%), the incidence of PONV were high onfemale gender within 14 patients (51,9%), the incidence of PONV were high in 3 age groups 18-24 years, 25-31 years and39-45 years within 6 patients (22,2%), the incidence of PONV were high on ENT operative procedures within 11 patients(40,7%), the incidence of PONV were high on non-smokers within 21 patients (77,8%). In this study the highest incidence ofPONV was found in the age group 18-24 years, 25-31 years, and 39-45 years, female gender, undergone ENT operativeprocedures, and non-smokers patients.